Dampak New Southern Policy Korea Selatan Terhadap Sektor Ekonomi dan Pertahanan Indonesia - Pasha, Auralia Salsabila Tuada; Paksi, Arie Kusuma (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
South Korea’s economy has been heavily depend on major power countries such as US, China, Japan, and Russia. However, with the changing dynamics in international world such as growing protectionism in US during Trump leadership, China’s expansion of influence in Asia, as well as trade war between US and China causing President Moon Jae In to switch South Korea’s economy horizon. New Southern Policy is a diplomatic initiative established to reduce those dependence. South Korea invites India and ASEAN as its brand new partners. South Korea stated that Indonesia is a major partner in New Southern Policy. This research aims to analyze the impact of New Southern Policy in Indonesia, especially in economy and defense sectors. The impact on economy sectors are both countries agreed to signed IK-CEPA agreement, South Korea which eager to make Indonesia as new production base in ASEAN through Hyundai company factory construction, and LG Consortium investment in the electric vehicle battery cell industry. Moreover, the impact on defense sectors is joint venture project for the production of KFX/IFX fighter jets.